An analytical study of the mechanics of the thrower's position at the end of the rotation and a comparison between the world and Iraqi champions in the discus throw event (Damu Journal of Sport Sciences, 2024)
The study aimed to identify the results of the analytical mechanics of the thrower's position at the end of the rotation and a comparison between the world and Iraqi champions in the discus throw event.The research sample included the world and Iraqi champions in the discus throw event, as the researcher analyzed a CD containing a photograph of the world champion and the Iraqi champion in the discus throw event in their best achievements, and the method followed at the end of the rotation phase was highlighted.After presenting, analyzing and discussing the results in the third chapter, it became clear that there were differences in some body angles between the two champions. The researcher concluded that the world champion was better in performance compared to the Iraqi champion by a large margin.There were a set of recommendations, including the researcher recommending that Iraqi trainers rely on the results of this study and apply them to discus throwers during their training, due to their importance in achieving the best performance and their positive impact on the distance achieved.